Effects of Eight Week Supplementation of Ashwagandha and Amalaki Churna as a Rasayana w.r.t General Physical Fitness and Cardio-respiratory Endurance - Shilpi Mehra,; Vijay Chaudhary, (International Journal of Ayurveda and Pharma Research, 2024)
In India and around the world, people are spending more and more time enjoying sedentary lifestyle. This type of lifestyle decreases our physical fitness and compromises our cardio respiratory endurance. Under such circumstances along with a dynamic change in lifestyle and enhanced physical activity, there arises a need of drugs which can improve the physical fitness and cardio respiratory endurances among the youngsters and the adults. Purpose: The aim of the present study was to evaluate the efficacy of Ashwagandha and Amalaki Churna as a Rasayana with respect to general physical fitness and cardio-respiratory endurance. Material and Methods: 60 healthy individuals were registered for the present study. The individuals were divided into four groups. Each group comprised of 15 individuals. Group-I individuals were given Amalaki Churna, group-II individuals were given Ashwagandha Churna, group-III individuals were given both Ashwagandha and Amalaki Churna and group-IV individuals were given starch capsules as placebo therapy. The Ashwagandha and Amalaki Churna were given in the dose of 5gm each. Outcome measures: The study subjects were asked to perform tread mill test and TMT related parameters like exercise time, work load attained in terms of Mets, VO2 max, heart rate reserve index and rate pressure product were measured both before and after the completion of 8 weeks of therapy. Apart from this vital capacity and BMI were also measured. Results: After the therapy there was a statistically significant improvement in general physical fitness and cardiorespiratory endurance on various parameters in group-I, group-II, group-III, whereas placebo group did not show any statistically significant improvement. Conclusion: Ashwagandha and Amalaki improved the general physical fitness and cardiorespiratory endurance of the individuals.